Investigating The Effect of Blended Learning On Students’ Grammar Achievement - Haryati, Haryati (CV. Pena Persada, 2018)
This study was aimed at investigating the effectiveness of blended learning using e-learning software on students‘ grammar achievement. To obtain the data, 40 English literature students at fourth semester of Pamulang university were chosen as participants in this study. 20 evening class students were the experimental groups, and 20 morning class students were control group. Each group had different treatment which experimental group had blended learning while control group had traditional learning experience. Grammar test and questionnaire were administered in order to have the real students‘ scores and find out the students‘ perception of blended e-learning. A quantitative analysis including descriptive statistics and independent t test were further analysed in order to investigate the effects of blended e-learning on students‘ grammar achievement. The result revealed that p – value < 0.05 which means two groups showed significant difference. In other words, blended e-learning presented positive effect on students‘ grammar achievement.